The temporal association between social isolation, distress, and psychotic experiences in individuals at clinical high-risk for psychosis - Akcaoglu, Zeynep; Vaessen, Thomas; Velthorst, Eva; Lafit, Ginette; Achterhof, Robin; Nelson, Barnaby; McGorry, Patrick D.; Schirmbeck, Frederike; Morgan, Craig; Hartmann, Jessica A.; Gaag, Mark van der; Haan, Lieuwe de; et al. (Psychological medicine, 2024)
BackgroundPsychotic experiences (PEs) and social isolation (SI) seem related during early stages of psychosis, but the temporal dynamics between the two are not clear. Literature so far suggests a self-perpetuating cycle wherein momentary increases in PEs lead to social withdrawal, which, subsequently, triggers PEs at a next point in time, especially when SI is associated with increased distress. The current study investigated the daily-life temporal associations between SI and PEs, as well as the role of SI-related and general affective distress in individuals at clinical high risk (CHR) for psychosis.MethodsWe used experience sampling methodology in a sample of 137 CHR participants. We analyzed the association between SI, PEs, and distress using time-lagged linear mixed-effects models.ResultsSI did not predict next-moment fluctuations in PEs, or vice versa. Furthermore, although SI-related distress was not predictive of subsequent PEs, general affective distress during SI was a robust predictor of next-moment PEs.ConclusionsOur results suggest that SI and PEs are not directly related on a moment-to-moment level, but a negative emotional state when alone does contribute to the risk of PEs. These findings highlight the role of affective wellbeing during early-stage psychosis development.